Biology communication skills: Engaging innovations with 'two stay, two stray - Leasa, Marleny; Rengkuan, Mariana (Universitas Negeri Jakarta, 2025)
One of the essential skills needed by prospective elementary education teachers is scientific communication. The issue raised is the low level of communication skills among students in the context of relevant biological issues, which can hinder their engagement in biology science discussions and evidence-based decision-making. This study aims to analyze the scientific communication skills of prospective science teachers in biological science concepts. The research adopts a descriptive approach in its methodology. The research process was conducted through direct observation of learning activities taking place in the classroom. The population in this study consists of students from the elementary teacher education program at a public university in Ambon City, with a sample size of 80 students. The results indicate that the implementation of the Two Stay, Two Stray (TSTS) approach significantly improves students' communication skills. The average communication skills score increased by 71.41%, falling into the good category. These findings suggest that this collaborative approach is effective in enhancing students' understanding of biological issues and their ability to communicate effectively. This study recommends the implementation of active learning methods such as TSTS in science education to facilitate the development of scientific literacy and students' communication skills.